Structural equation modeling: An application of broadband penetration and GDP growth in Asia - Tasneem Fatima Alam; Nayeem Sultana; Md. Israt Rayhan (Journal of Economic Structures, 2019)
In the present era of globalization, broadband penetration which indicates access to high-speed internet has allowed the transferring of information in a way that was never observed before. With the growing world-wide investment and attention received by broadband infrastructure, this study examines the relationship between broadband penetration and economic growth with a panel data consisting of ten Asian countries over 2001-2015. This study uses a structural equation modeling approach to estimate the relationship between endogenous broadband penetration and economic growth through two-stage least squares, three-stage generalized method of moments and full-information maximum likelihood estimation. A positive and significant impact of broadband penetration on economic growth is found controlling individual effect of countries.
Keywords: 330; Broadband; GDP growth; Structural modeling; 3SLS; FIML